E-Service Quality Application for Teacher Performance Assessment Using the Servqual Method - Angelina Angelina; Gusrio Tendra (Journal of Applied Business and Technology, 2026)
Teacher performance assessment is a crucial aspect of improving the quality of education. However, manual assessment processes are often inefficient and time-consuming. Therefore, this study develops an E-Service Quality application aimed at evaluating teacher performance more effectively using the SERVQUAL method. The SERVQUAL method is used to measure service quality based on five key dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This application allows educational staff to assess teacher performance based on predefined indicators. The collected data is then analyzed to identify gaps between user expectations and the received service quality. The research results indicate that the implementation of the E-Service Quality application can enhance transparency and objectivity in teacher performance assessment. Additionally, this application provides faster and more accurate result, making it a valuable tool for decision-making in improving teaching quality.